174G>C interleukin-6 gene polymorphism in Tunisian patients with coronary artery disease - Ghazouani, Lakhdar; Abboud, Nesrine; Khalifa, Sonia Ben Hadj; Added, Faouzi; Khalfallah, Ali Ben; Nsiri, Brahim; Mediouni, Mounira; Mahjoub, Touhami (Annals of Saudi medicine, 2011)
A state of low-grade inflammation accompanies the pathogenesis of atherosclerotic events. Interleukin-6 (IL-6) is a pleotropic pro-inflammatory cytokine that modulates the development of acute coronary syndromes (ACSs), partly by destabilizing coronary atherosclerotic plaques. We have examined the contribution of the -174G>C IL-6 promoter variant on the risk of coronary artery disease (CAD) among Tunisians. Study subjects included 418 CAD patients and 406 age- and sex-matched controls. IL-6 genotyping was done by PCR-restriction fragment length polymorphism. The frequency of the -174C allele (mutant) was lower in Tunisians than in Europeans, and the distribution of -174 G>C genotypes was similar between CAD patients and control subjects. Moreover, compared to GG genotype carriers, -174C allele carriage did not increase the CAD relative risk (odds ratio and 95% confidence interval=1.09 and 0.80-1.49), which remained nonsignificant after adjusting for traditional risk factors for CAD (age, smoking, hypertension, diabetes and obesity). The -174G>C IL-6 promoter variant is not associated with an increased risk of CAD among Tunisians.